Gagasan Maqashid Syariah Jasser Audah dan Implementasinya dalam Bidang Ekonomi dan Keuangan Syariah - Suryana, Anisa Maulita; Muhajirin (Universitas Muhammadiyah Prof. DR. HAMKA, 2024)
The concept of maqashid syariah is a fundamental framework in Islamic law aimed at protecting five essential needs: religion, life, intellect, lineage, and wealth. Jasser Audah's thought introduces a systemic and holistic approach to maqashid syariah, relevant for addressing contemporary challenges in Islamic economics and finance. This study aims to analyze Audah’s contributions in advancing Islamic economics through the application of maqashid syariah in investment and risk management. The research method involves a literature review with a descriptive-analytical approach, focusing on maqashid syariah concepts in academic books and journals. The results indicate that maqashid syariah, when comprehensively applied, can enhance social justice and community welfare.In conclusion, maqashid syariah provides a normative foundation to integrate Islamic principles into modern economics, creating a more sustainable and inclusive system.